Employee satisfaction with the physical work environment: the importance of a need based approach - Budie, Bart; Appel-Meulenbroek, Rianne; Kemperman, Astrid; Weijs-Perree, Minou (International Journal of Strategic Property Management, 2019)
Employee satisfaction is pivotal for companies as it enhances perceived productivity and organizational performance. Office concepts and their workspaces can affect employee satisfaction. However, these effects are still ambiguous, particularly regarding the activity-based concept. Therefore, in this study employee satisfaction with the work environment is investigated from a holistic approach. The effects of both personal characteristics and workspaces used by the employee on work environment satisfaction are described and measured, including mediating effects of the perceived importance of employee needs. Data was collected using an online questionnaire among 327 employees of 13 knowledge-based organizations. Path analysis was used to determine the direct and indirect effects of personal variables, environmental variables and perceived importance of needs on satisfaction. It demonstrated that both personal and environmental variables affect satisfaction, and that a considerable number of these effects are indirect through the perceived importance of needs. In particular, the effects of used workspaces were extensive.First Published Online: 30 Nov 2018